Analisis Strategi Sekolah dalam Mendorong Implementasi Kompetensi Kepribadian Guru di SMA - Pratama, Della Marsya; Irma, Ade (CV. Lentera Literasi Indonesia, 2025)
Personality competence is a fundamental element that every teacher must possess, particularly at the senior high school (SMA) level, where students experience complex developmental dynamics. This competence reflects a teacher’s integrity, emotional maturity, exemplary conduct, and ability to build positive relationships within the school environment. This article aims to analyze effective strategies and efforts for implementing personality competence among high school teachers. Using a qualitative approach based on literature review and in-depth interviews, this study identifies several key strategies, including personality training based on values and professional ethics, the establishment of teacher communities for emotional support and professional sharing, the development of a positive and reflective school culture, and the provision of regular self-reflection opportunities for teachers. In addition, the active involvement of school leadership, particularly principals and educational managers, is found to be a determining factor in creating a sustainable system that supports the continuous development of teachers’ personality competence. The findings are expected to serve as a practical reference for schools in improving the quality of education through strengthening the character and integrity of educators.